Studying the strength and damageability of composite element in looped metal-composite joint under tensile loading (Fracture and Structural Integrity, 2025)
The article presents the results of computational and experimental studies of the strength and damageability of a connecting composite part in a metal-composite joint of isogrid and anisogrid structures made of polymer composite material under tension. The assessment of the minimal cross-sectional area of the connecting part was performed based on design calculations, taking into account strengthening during extrusion of the excess binder. The onset of failure in the contact zone with the steel element of the metal-composite joint was predicted based on experimental studies using model samples. A comparison was made between the calculation results for the tensile loading diagram, considering the physical nonlinear behavior of composite material in the joint zone, and the readings of strain gauges after testing the metal-composite joint. Damages and deformation of the connecting composite part under the tensile load was imaged using acoustic microscopy.
Keywords: aircraft structures; polymer composite materials; carbon fiber reinforced polymers; metal-composite joint; finite element method; acoustic microscopy